Endoscopic biopsy techniques in Barrett esophagus patients: a multidesign study - Beaufort, Ilse N.; Elias, Sjoerd G.; Akkerman, Elisabeth M.P.; Milne, Anya N.; Brosens, Lodewijk A. A.; Verhagen, Marc A. M. T.; Alvarez Herrero, Lorenza; Weusten, Bas L. A. M. (Endoscopy, 2025)
The impact of different random biopsy techniques for Barrett esophagus (BE) surveillance on histopathological quality is unclear. We compared the double- vs. single-biopsy method and advance-and-close vs. turn-and-suction technique.In a multicenter, factorial design trial (Part I), BE patients were randomly assigned to the double- or single-biopsy method and advance-and-close or turn-and-suction technique (1:1:1:1). In a before–after study (Part II), the optimal biopsy method and technique were implemented in clinical practice. The primary end point in both parts was biopsy size.In Part I (107 patients, 1024 biopsies), single-method biopsies were 25% larger than double-method biopsies (3.34 mm2 [95%CI 3.10–3.57] vs. 2.68 mm2 [95%CI 2.45–2.92]; P < 0.001). Mean (95%CI) biopsy size was 2.95 mm2 (2.72–3.19) and 3.08 mm2 (2.85–3.31) with advance-and-close and turn-and-suction techniques, respectively (P = 0.44). The interaction term between the co-primary comparisons was P = 0.08. Mean (95%CI) biopsy size for double-biopsy + advance-and-close, double-biopsy + turn-and-suction, single-biopsy + advance-and-close, and single-biopsy + turn-and-suction was 2.77 mm2 (2.44–3.09), 2.61 mm2 (2.29–2.93), 3.14 mm2 (2.81–3.46), and 3.54 mm2 (3.22–3.86), respectively. In Part II, 46 and 44 patients were included before and after implementation of the single-biopsy method and turn-and-suction technique, in whom this combination was used in 16/46 (35%) and 44/44 (100%) patients, respectively. Mean (95%CI) biopsy size increased by 18%, from 3.31 mm2 (2.95–3.68) to 3.90 mm2 (3.50–4.29; P = 0.03).BE surveillance biopsies should be taken with the single-biopsy method and turn-and-suction technique to increase biopsy size.BE surveillance biopsies should be taken with the single-biopsy method and turn-and-suction technique to increase biopsy size.